Media Education in Action A Research Study in Six European Countries - Parola, Alberto (Strumenti per la didattica e la ricerca, 2010)
Media Education (ME) has come a long way. Today, it can no longer be considered a field of study reserved for semiotic and communication researchers. Nor can it be regarded as a privileged practice of those teachers, who for some reason consider media of fundamental importance. On one hand, ME is now part of the agenda of international organizations, which consider the development of media competences a necessary requisite to fully exercise citizenship in the current contemporary society. On the other, ME practices are becoming increasingly widespread in schools involving a growing number of teachers. Notwithstanding, teaching the media still seems to be a rather solipsistic task where «everything is fine». Indeed, in ME there is a tremendous lack of research concerning the educational practices' quality and effectiveness. This book tries to cope with these issues by providing a set of instruments to design, develop and evaluate ME activities in schools, and supporting the enhancement of media educators' knowledge and skills.